From monastic rules to religious constitution - SZEWCZUL, BOŻENA (Prawo Kanoniczne, 2017)
Main intention of the Author’s article is showing the essence and meaning of the religious constitution, and restore their proper position in modern religious life, as well as due respect and appreciation of their value by the religious. Therefore the starting point for her was referring to first norms of life dedicated to God in the Catholic Church, that is to monastic rules, and regard, or even cult, which was shown by Pachomian, Basilian, Augustinian, Benedictine monks, as well as St Franciscan Minor Brothers. Author’s research shows, that old rules as well as modern religious constitutions - which are their continuation - deserve the respect. They are strongly related to the Sacred Scriptures, for instance showing faithful way of following Christ, and also including spirituality of the religious institute founder, which results from charisma given by the Holy Ghost for the benefit of the institute members, and the whole Church. Membership of the specific institution requires keeping and developing thoughts, as well as the intentions of the founder, that is so called spiritual inheritance, which can be generally learnt due to the reading of the constitutions left by him.